Convective System Observations by LEO and GEO Satellites in Combination - Tran Vu La (IEEE, 2021)
The combination of low earth orbit (LEO) and GEO stationary (GEO) satellites brings significant advantages to observe, monitor, and understand convective systems and the associated vertical and horizontal dynamics. Two LEO, C-band Sentinel-1 synthetic aperture radar and L-band soil moisture active passive (SMAP) radiometer, are used to observe surface wind patterns, while the other LEO (Aeolus lidar instrument) offers the measurements of intense convective downdrafts. Meteosat GEO is used to detect deep convective clouds. Four case study examples of LEO and GEO combination illustrate here the matching in location and observation time between deep convective clouds, intense downdrafts, and strong surface wind gusts. In particular, the two-dimensional deep convective cloud patterns and surface wind patterns have the same direction displacement. The observations of surface wind patterns by two different LEO (Sentinel-1 and SMAP) indicate that the high-intensity radar backscattering on Sentinel-1 images should be induced by convective wind gusts rather than hydrometeors or convective precipitation at the sea surface as suggested in previous references. Finally, the convective wind gusts estimated from Sentinel-1 and SMAP data correspond to those obtained by the high-frequency radars, small-scale numerical models, and in-situ measurements.